2008
DOI: 10.1002/cmdc.200800145
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Novel Non‐Cyclam Polynitrogenated CXCR4 Coreceptor Inhibitors

Abstract: HIV cell fusion and entry have been validated as targets for therapeutic intervention against infection. Bicyclams were the first low-molecular-weight compounds to show specific interaction with CXCR4. The most potent bicyclam was AMD3100, in which the two cyclam moieties are tethered by a 1,4-phenylenebis(methylene) bridge. It was withdrawn from clinical trials owing to its lack of oral bioavailability and cardiotoxicity. We have designed a combinatorial library of non-cyclam polynitrogenated compounds by pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(35 citation statements)
references
References 92 publications
1
33
0
Order By: Relevance
“…This is additional evidence these molecules may be associated with tumor resistance to anti-angiogenic therapy. The expression of SDF1α and CXCR4 has been strongly implicated in tumor growth, promoting cell migration and the recruitment of cells implicated in the revascularization process in tumors [17, 4447]; this strongly suggested that SDF1/CXCR4 assists tumors in evading anti-angiogenic therapy. The microenvironment contribution in GBM development is increasingly emphasized.…”
Section: Discussionmentioning
confidence: 99%
“…This is additional evidence these molecules may be associated with tumor resistance to anti-angiogenic therapy. The expression of SDF1α and CXCR4 has been strongly implicated in tumor growth, promoting cell migration and the recruitment of cells implicated in the revascularization process in tumors [17, 4447]; this strongly suggested that SDF1/CXCR4 assists tumors in evading anti-angiogenic therapy. The microenvironment contribution in GBM development is increasingly emphasized.…”
Section: Discussionmentioning
confidence: 99%
“…[17] Based on this evidence, we designed a library of new monocyclam derivatives which combine the cyclam ring with the diamines used in our previous work. [17] A selection of the presumably most active compounds (2 and 3) was accomplished with published virtual screening methods. [18] Here, we report on the synthesis, binding mode studies and anti-HIV activity of these two novel monocyclam derivatives.…”
Section: Rational Design Of Monocyclam Derivativesmentioning
confidence: 99%
“…MSX-122 ( Fig. 1) is the lead compound of this class [25,26]. Orally bioavailable functionalized isothioureas were found to be potent and selective CXCR4 antagonists ( Fig.…”
Section: Introductionmentioning
confidence: 99%